NON-REFOULMENT PRINCIPLE AND PROHIBITION OF ENTRY FOR REFUGEES DUE TO THE COVID-19 PANDEMIC - FX. Joko Priyono; Audrey Kartika Putri (Diponegoro Law Review, 2022)
The principle of non-refoulement has become jus cogens which obliges every country, both ratifying and not ratifying the 1951 Refugee Convention and the 1967 Protocol not to refuse refugees and asylum seekers to enter the territory of a country and not be returned to their country of origin because their lives will be threatened, persecuted. and tortured. The right to life is a right that cannot be reduced and must be protected and respected by everyone under any circumstances. The pandemic reason cannot be used as an excuse to refuse refugees and asylum seekers on the grounds of protecting the right to health for its citizens. Efforts to quarantine asylum seekers and refugees suspected of or affected by Covid-19/Omicron is a policy that is in accordance with human rights as well as according to the principle of non-refoulement.